hanna73820
hanna73820
01-09-2015
Mathematics
contestada
6m - 11 = 2 + 9m - 1
Respuesta :
SugarShane502
SugarShane502
01-09-2015
6m-11=2+9m-1. First factor out what you know so the problem simplified will be 6m-11=9m+1. Next step add 11 to both sides which changes the problem to 6m=9m+12. Subtract 9m from both sides to get -3m=12. Divide by -3 to get m by itself. M= -4
Answer Link
VER TODAS LAS RESPUESTAS ( 57+ )
Otras preguntas
Manipulate the following equation to solve for t: (1 point) s = 1/2 a t^2
2/7 with an exponent of 3
According to Erikson, at what age does the trust versus mistrust stage occur?
Tiffany sketched a picture is a car she used the scale 2 inches:12 feet the car in her sketch is 8 inches long what is the length in feet of the actual car
which equation shows y=3/4x -5/2 in a standard form?3x-4y=104x-3y=103x-4y=-104x-3y=-10
Choose the point-slope form of the line passing through (3.5) with a slope of -3. O y– 3 = -3 (x – 5) o =3(y – 5) = 2-3 O y - 5 = -3 (2-3) o 30 – 5y = -3
If a source radiates sound uniformly in all directions and you triple your distance from the sound source, what happens to the sound intensity at your new posit
Starting in 2012, students began taking the ________ exam to assess their academic progress.
Help, I know D2 is the dilation of 2? And I know the rotation is 90 degrees but I’m not to sure on how to find my answer? Help please
True or False. A law is passed that makes community college tuition free for all U.S. citizens.